A Comparative Study of Aspiration versus Non-aspiration Technique in Fine Needle Cytology of Thyroid Lesions - Shah, Anita; Shrestha, Ashmita; Poudel, Anuj; Samdurkar, Ashok P; Chaurasiya, Anand; Gurmaita, Raman Kumar (Med Phoenix, 2024)
Introduction: Fine needle aspiration cytology (FNAC) is a well-established procedure used in diagnosis of palpable thyroid swelling. This technique is practiced worldwide and is investigation of choice in thyroid swelling. Fine needle non- aspiration cytology (FNNAC) avoids aspiration, uses capillary action. It is patient friendly with less pain and better perception of lesion. Hence present study was conducted to compare effectiveness of aspiration versus non- aspiration techniques for better specimen and cytological diagnosis in thyroid swellings. Materials and Methods: All patients who fulfilled the inclusion criteria were subjected to both FNAC and FNNAC techniques performed simultaneously at the same site. The study period was March 2020 to March 2021 at Universal College of Medical Sciences Teaching Hospital, Bhairahawa (UCMS-TH). Points were allocated to each specimen according to Mair et al. scoring system and categorized. All the lesions were analysed statistically by using Statistical Package for Social Sciences (SPSS) version 11.5. Results: Total 79 cases of thyroid swelling were evaluated and there was significant difference (p < 0.0001) of the background blood/clot, amount of cellular material, degree of cellular trauma, and degree of cellular degeneration and retention of appropriate architecture. Diagnostically superior smears were obtained in 39 cases by both FNAC and FNNAC technique. The most common cytological impression was Autoimmune Thyroiditis and Benign Follicular Nodule. Conclusion: FNNAC yields diagnostically better quality smears, while FNAC assures diagnostically adequate material quantitatively. Combining both FNNAC and FNAC can offer superior quality of the cytological material and quantity.